Factors influencing the intention to purchase health insurance: a study of Indian tobacco and alcohol consumers - Ashok Mishra; Mohammed Jamshed; Asad Ahmad; Swati Garg; Dag Øivind Madsen (Frontiers Media S.A., 2024)
IntroductionThis study empirically investigates the attitude of tobacco and alcohol consumers towards health insurance purchase in India. The study aims to determine the factors which plays a significant role in determining the purchase intention of health insurance among tobacco and alcohol consumers.MethodsWe propose an extended theory of planned behavior (TPB) model comprising factors like attitude, subjective norms, perceived behavior control, perceived usefulness, perceived product risk, and intention to purchase. We collected responses from 420 tobacco and alcohol consumers through a Google Form link shared via different social media platforms. SPSS has been used to perform exploratory factor analysis, whereas AMOS has been used to validate the constructs, confirm the relationships among the variables, and analyze the data.ResultsThe analysis outcomes demonstrate that subjective norms, perceived product risk, and perceived behavioral control are the factors that have a positive and significant effect on health insurance purchase intention among consumers.DiscussionThis research offers valuable insights to the insurance sector, government officials, policymakers, and academicians. Insurance companies may consider the criteria analysed when creating policies to promote the expansion of the health insurance sector.